Formation of MoO₃ crystals in electric arc plasma source - Lebid, A.V.; Veklich, A.N.; Boretskij, V.F.; Kolesnyk, O.G.; Savenok, S.P.; Andreev, O.V. (Вопросы атомной науки и техники, 2014)
Formation of molybdenum trioxide crystals by electric arc discharge between molybdenum electrodes is considered. Molybdenum oxide crystals were deposited on side surface of anode. Observation of crystals formation zone was used for determination of main formations stages. Plasma temperature was estimated by optical emission spectroscopy method. The resulting products were studied by X-rays diffraction, time-of-flight laser mass-spectrometry and optical microscopy methods. It was found, that self-organizing vapor-deposition process of MoO₃ crystals formation has place. The resulting product is colorless sparkling prisms and platelets, which are mainly consist of orthorhombic α-MoO₃ phase. Optical microscopy indicates the formation of closely packed feather-like pin structures by vapor-solid process.